Reputasi Bank Umum Syariah: Islamic Social Reporting, Islamic Corporate Governance, Ukuran Perusahaan, dan Kinerja Keuangan - Umiyati Umiyati; Alim Saparuddin Harahap (INSTITUT AGAMA ISLAM SEBI, 2026)
This study aims to analyze the influence of Islamic Social Reporting, Islamic Corporate Governance, Company Size and Financial Performance on the Reputation of Islamic Commercial Banks. The population in this study were 13 Islamic Commercial Banks in Indonesia registered with the OJK. The sample was selected using the Purposive Sampling method, with a total of 10 Islamic Commercial Banks analyzed. The type of data used is secondary data sourced from the annual report of each Islamic Commercial Bank in Indonesia for the period 2018-2023. Data analysis uses panel data regression with an analysis tool in the form of Eviews Version 12.0. The results of the study indicate that simultaneously there is an influence between Islamic Social Reporting (ISR), Islamic Corporate Governance (ICG), Company Size and Financial Performance (ROA) on Reputation of Islamic Commercial Banks. Partially, Islamic Corporate Governance (ICG) and Company Size have a significant effect on the Reputation of Islamic Commercial Banks, while Islamic Social Reporting (ISR) and Financial Performance (ROA) do not have a significant effect on the Reputation of Islamic Commercial Banks.